(untitled) (Journal of Student Affairs in Africa, 2021)
The year 2020 is a year that we will remember globally in higher education as having been most unusual, indeed, traumatic. If at the beginning of 2020 the year had a hopeful ring with plenty, as it comes to an end it is hard to just try and make sense of the extent that theexperience of higher education has been changed so incisively within a short time for both staff and students. And the signs are already there that the post-Covid-19 period will not be short of new challenges either. Challenges like addressing the increased mental health issues students suffer due to the crisis, illness, loss of loved ones and more. Moreover, there are many student groups whose ability to learn has been severely impacted by the pandemic and lockdown, including students from poor households, rural students, and students with special needs. As we noted in our last editorial, for these students, the campus environment and the services offered by Student Affairs departments is normally able to level the ’playing field’ of learning. It will require yet another extra effort by student affairs professionals, academics, administrators, fellow students and the communities and families to ensure that these students can catch up and have access to the same quality and quantity of learning opportunities within supportive contexts over the course of their studies as others who have been less impacted.